Pharmaceutical care for older adults in Brazil: a systematic review - Maria Olívia Barboza Zanetti; Ana Flávia Miguel dos Santos; Débora Ferreira Santos; Leonardo Régis Leira Pereira (Federal Council of Pharmacy, 2021)
Considering the specific requirements of the older adults in the use of drugs and the opportunity for the clinical pharmacist to contribute to these patients, this review aimed to identify studies that have evaluated the results of pharmaceutical care for older adults in Brazil. We conducted a systematic review of the studies that answered the following guiding question: "What pharmaceutical care outcomes in older adult patients are found in Brazil?". The search strategy was applied to the following databases in February 2019: PubMed, CENTRAL, BVS, and LILACS. Observational or experimental studies describing the results of pharmaceutical care in older adults in Brazil at any level of healthcare and related to the monitoring of any health problem were included. The quality of the included publications was assessed using the Downs and Black checklist. Of the 5080 studies that were identified, 11 were included. The results could summarize evidences supporting pharmaceutical care for older adults, regardless of place of attendance, health problem, or level of health care. The experiences of the Brazilians have contributed to the improvement of clinical and humanistic outcomes, such as reduction in blood pressure, glycemic index, lipid levels, anthropometric measurements, and polypharmacy; resolution of drugs related problems; and improvement in adherence and quality of life. One publication also reported economic outcomes (ICER per QALY gained). Although the number of articles obtained was small, they reported unanimously beneficial results. Pharmacist's training in healthcare service is essential for expanding pharmaceutical care for this population group.